Biodiversity in tropical plantations is influenced by surrounding native vegetation but not yield: A case study with dung beetles in Amazonia - Beiroz, Wallace; Barlow, Jos; Slade, Eleanor M.; Borges, Cézar; Louzada, Julio; Sayer, Emma J. (Forest ecology and management, 2019)
[Display omitted] •Plantations surrounded by native forest has more functional diversity.•Local and landscape features drive the differences between native and planted forest.•Biodiversity was not related to the timber production intensity.•Managing native forests in landscapes can enhance diversity in plantations.•Integrative management can improve biodiversity in plantations regardless of production. Human-modified forests, including plantations and managed forest, will be a major component of tropical landscapes in the near future. To conserve biodiversity across modified tropical landscapes we must first understand what influences diversity in planted areas. We studied dung beetle communities in Eucalyptus plantations to assess the influence of local (canopy openness and soil texture) and landscape factors (surrounding native forest cover) on taxonomic and functional diversity, and to determine whether biodiversity in plantations is affected by timber production. Dung beetle community composition in Eucalyptus plantations was largely explained by the surrounding native forest cover, as Simpson’s diversity and functional diversity (Rao’s quadratic entropy) increased with the extent of native forest in buffer areas. However, the abundance of dung beetle species associated with native forest was not explained by any of the explanatory variables. The coarse sand content of the soil explained much of the functional similarity between plantations and native forests, as well as variation in dung beetle community structure. The total abundance of dung beetles in plantations increased with coarse sand content, whereas body mass declined, and dung beetle abundance and functional originality decreased with canopy openness. Timber production intensity did not explain the variation in any of the measured diversity parameters. If enhancing biodiversity in plantations is a management goal, then these results highlight the importance of restoring or retaining native forest areas in modified landscapes. They also suggest that integrated management could improve biodiversity in Eucalyptus plantations without reducing timber production.